2018
DOI: 10.14814/phy2.13628
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and protein complex co-localization of mTOR is associated with postprandial myofibrillar protein synthesis at rest and after endurance exercise

Abstract: Translocation and colocalization of mechanistic target of rapamycin complex 1 (mTORC1) with regulatory proteins represents a critical step in translation initiation of protein synthesis in vitro. However, mechanistic insight into the control of postprandial skeletal muscle protein synthesis rates at rest and after an acute bout of endurance exercise in humans is lacking. In crossover trials, eight endurance‐trained men received primed‐continuous infusions of L‐[ring‐2H5]phenylalanine and consumed a mixed‐macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 60 publications
7
50
0
Order By: Relevance
“…The cellular mechanisms that regulate myofibrillar protein synthesis rates are assumed to be centered on anabolic pathways such as mTORC1 signalling (Abou Sawan et al . ). We previously showed dysregulated mTORC1 signalling in muscles of obese vs .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cellular mechanisms that regulate myofibrillar protein synthesis rates are assumed to be centered on anabolic pathways such as mTORC1 signalling (Abou Sawan et al . ). We previously showed dysregulated mTORC1 signalling in muscles of obese vs .…”
Section: Discussionmentioning
confidence: 97%
“…Given that the synthesis rates of myofibrillar protein fraction were robustly stimulated in the NW group at 0-2 h compared to the OB group, it appears that perhaps with resistance exercise the dietary amino acids remained confined to the more rapidly turning over sarcoplasmic pool in obese muscles as opposed to being used for post-exercise myofibrillar protein accretion. J Physiol 596.21 The cellular mechanisms that regulate myofibrillar protein synthesis rates are assumed to be centered on anabolic pathways such as mTORC1 signalling (Abou Sawan et al 2018). We previously showed dysregulated mTORC1 signalling in muscles of obese vs. normal weight adults (Beals et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, protein co-ingestion did not result in greater MitoPS rates than 0 g PRO ( Figure 11A , B ). MitoPS rates increase in response to intravenous infusion of amino acids ( 19 , 20 ), and the ingestion of larger (i.e., 36 g) ( 21 ), but not smaller (i.e., 18 g) ( 18 ) doses of protein at rest. Our finding that protein co-ingestion did not result in greater MitoPS rates than 0 g PRO aligns with previous studies that reported no further increase in MitoPS rates after protein intake compared with a nonprotein control during recovery from endurance exercise ( 13 , 14 ) or combined endurance and resistance exercise ( 22–24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that protein co-ingestion did not result in greater MitoPS rates than 0 g PRO aligns with previous studies that reported no further increase in MitoPS rates after protein intake compared with a nonprotein control during recovery from endurance exercise ( 13 , 14 ) or combined endurance and resistance exercise ( 22–24 ). Studies to date examining the impact of protein ingestion on MitoPS rates after an acute bout of endurance exercise or combined endurance and resistance exercise have provided protein doses < 30 g ( 13 , 14 , 18 , 22–24 ). Our results show that even relatively large doses of protein (45 g or ∼0.58 g protein/kg) do not increase MitoPS rates more than the ingestion of carbohydrate only during the first few hours of recovery from a single bout of endurance exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation